Treatment outcomes of transoral robotic and non-robotic surgeries to treat oropharyngeal, hypopharyngeal, and supraglottic squamous cell carcinoma: A multi-center retrospective observational study in Japan. Issue 3 (June 2021) - Sano, Daisuke; Shimizu, Akira; Tateya, Ichiro; Fujiwara, Kazunori; Mori, Terushige; Miyamoto, Shunsuke; Nishikawa, Daisuke; Terada, Tomonori; Yasumatsu, Ryuji; Ueda, Tsutomu; Matsumoto, Fumihiko; Kishimoto, Yo; et al.
Abstract: Objectives: The aim of this multicenter retrospective cohort study was to compare efficacy and subsequent postoperative treatment between transoral robotic surgery (TORS) and any non-robotic transoral surgery in Japanese patients with early oropharyngeal squamous cell carcinoma (OPSCC), hypopharyngeal SCC (HPSCC), or supraglottic SCC (SGSCC). Materials and methods: Clinical information and surgical outcomes were compared between patients with early-stage OPSCC, HPSCC, and SGSCC who underwent TORS (TORS cohort) and those who underwent non-robotic transoral surgery, including transoral videolaryngoscopic surgery (TOVS), endoscopic laryngopharyngeal surgery (ELPS), and transoral laser microsurgery (TLM) (non-robotic cohort). The data of the Head and Neck Cancer Registry of Japan (registry cohort) were used to validate the comparison. The main outcomes were the presence of positive margins under pathology and the requirement for postoperative therapy, including radiotherapy or chemoradiotherapy. Results: Sixty-eight patients in the TORS cohort, 236 patients in the non-robotic cohort, and 1, 228 patients in the registry cohort were eligible for this study. Patients in the TORS cohort were more likely to have oropharyngeal tumor disease and T2/3 disease than those in the other cohorts ( P <0.001 and P =0.052, respectively). The TORS cohort had significantly fewer patients with positive surgical margins than the non-robotic cohort ( P =0.018), as well as fewer patients who underwent postoperative treatment, although the difference was not significant ( P =0.069). In the subgroup analysis of patients with OPSCC, a total of 57 patients in the TORS cohort, 73 in the non-robotic cohort, and 171 in the registry cohort were eligible for the present study. Patients with OPSCC who underwent TORS were more likely to have lateral wall lesions than those in the other cohorts ( P =0.003). The TORS cohort also had significantly fewer patients with positive surgical margins than the non-robotic cohort ( P =0.026), and no patients in the TORS cohort underwent any postoperative treatment for OPSCC, although the difference was not significant ( P =0.177). Conclusions: Our results suggest that TORS leads to fewer positive surgical margins than non-robotic transoral surgeries. The clinical significance of TORS may be further validated through the results of all-case surveillance for patients who underwent TORS running in Japan in the future.